Integral system for automated fixture design (Journal of Production Engineering, 1994)
The paper presents an analysis of approach to rationalization and automation of fixture design. Based on the analysis, an integral approach to fixture design is defined. Further on, the paper reviews a model of the proposed system. The following parts of the system are given in detail: subsystem for input data definition, data files data bank main program containing subprograms for selection of the available fixtures and design (synthesis) of new fixtures with output data. The final part gives some verification results pertaining to the selection of the existing solutions of fixtures.
Keywords: fixture design; integral approach